Positive plate, lithium ion battery and positive plate preparation method

By using aluminum hydroxide as a flame retardant conductive primer in the positive electrode sheet of a lithium-ion battery, the contradiction between safety performance and electrical performance in the prior art is solved, and the improvement of safety performance and electrical performance is achieved. Keep it while reducing costs.

CN119480902APending Publication Date: 2025-02-18ICON ENERGY SYSTEM (SHENZHEN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411593322.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In order to improve the safety performance of lithium-ion batteries in the prior art, the electrical performance may be deteriorated or the membrane requirements and cost may be high.

Method used

The positive electrode sheet design is adopted, including a current collector, a flame-retardant conductive primer layer and a positive electrode active material layer. The flame-retardant conductive primer layer consists of aluminum hydroxide as the flame retardant, and conductive carbon black etc. as the conductive agent. By optimizing the particle size and ratio The relationship between surface area and resistivity satisfies the condition of 10≤ρ×r/A≤10000.

Benefits of technology

Improves the safety performance of lithium-ion batteries while maintaining good cycling performance, avoiding negative impacts on battery performance and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480902A_ABST
    Figure CN119480902A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a positive plate, a lithium ion battery and a preparation method of the positive plate. The positive plate comprises a current collector, a flame-retardant conductive priming coat and a positive active material layer; the flame-retardant conductive priming coat is laid on the surface of the current collector, and the positive active material layer is laid on the flame-retardant conductive priming coat; and the flame-retardant conductive bottom coating comprises a flame retardant and a conductive agent. The flame retardant is aluminum hydroxide, and the aluminum hydroxide meets the following relational expression: rho * r / A is more than or equal to 10 and less than or equal to 10000; wherein rho is the resistivity of the aluminum hydroxide, and the unit is omega.m; r is the particle size of aluminum hydroxide, and the unit is nm; a is the specific surface area of aluminum hydroxide, and the unit is m < 2 > / g. Preferably, the flame retardant is aluminum hydroxide, rho * r / A is larger than or equal to 10 and smaller than or equal to 10000, good cycle performance can be guaranteed, and safety performance can also be guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, in particular to a positive electrode sheet, a lithium ion battery and a method for preparing the positive electrode sheet. Background Art

[0002] Lithium-ion battery is a common rechargeable lithium-ion battery widely used in mobile devices, electric vehicles, energy storage systems and other fields. It consists of a positive electrode, a negative electrode, an electrolyte and a separator, where the positive electrode and the negative electrode are the storage and release locations of lithium ions respectively. However, since lithium-ion batteries contain flammable electrolytes, overcharging, over-discharging or physical damage may cause thermal runaway and cause safety issues.

[0003] Safety performance has always been an unavoidable issue for lithium-ion batteries. Although lithium-ion batteries have been commercially used on a large scale, the safety performance of the battery cells has not been completely resolved. Therefore, improving the safety performance of lithium-ion batteries is one of the important topics in the research and development of lithium-ion batteries. Currently, there are two main methods for improving the safety performance of lithium-ion batteries on the market. One is to apply a layer of lithium iron phosphate primer on the surface of the positive electrode current collector, and the positive electrode active layer is coated on the lithium iron phosphate primer. The lithium iron phosphate material itself has good stability and high safety performance, but poor conductivity, so this method will lose some of the electrical performance of the lithium-ion battery; the second is to increase the thickness of the diaphragm to reduce the thermal shrinkage of the diaphragm, but this solution has high requirements for the diaphragm and significantly increases the cost. Summary of the invention

[0004] The embodiments of the present invention provide a positive electrode sheet, a lithium ion battery and a method for preparing the positive electrode sheet to solve the problems in the prior art that the electrical performance of the lithium ion battery deteriorates or the separator has high requirements and high costs in order to improve the safety performance.

[0005] The invention discloses a positive electrode sheet, comprising a current collector, a flame retardant conductive primer layer and a positive electrode active material layer; the flame retardant conductive primer layer is laid on the surface of the current collector, and the positive electrode active material layer is laid on the flame retardant conductive primer layer; the flame retardant conductive primer layer comprises a flame retardant and a conductive agent;

[0006] The flame retardant is aluminum hydroxide, which satisfies the following relationship:

[0007] 10≤ρ×r / A≤10000

[0008] Wherein, ρ is the resistivity of aluminum hydroxide, in Ω·m; r is the particle size of aluminum hydroxide, in nm; A is the specific surface area of ​​aluminum hydroxide, in m 2 / g.

[0009] Optionally, the particle size of aluminum hydroxide is 1nm to 9um, and the specific surface area is 1 to 5m 2 / g, and the resistivity is 108~1012Ω·m.

[0010] Optionally, the conductive agent is one or more of conductive carbon black, graphene, carbon nanotubes, carbon nanorods, graphite, etc.

[0011] Optionally, the flame retardant accounts for 10% to 90% by mass in the flame retardant conductive primer layer.

[0012] Optionally, the conductive agent accounts for 5% to 35% of the flame retardant conductive primer layer by mass.

[0013] Optionally, the thickness of the flame retardant conductive primer layer is 1 um to 10 um.

[0014] Optionally, the flame retardant conductive primer layer further includes a binder, and the binder is one or more of polyvinylidene fluoride, polyimide, polyacetamide, polyacrylonitrile, polyacrylamide, and the like.

[0015] Optionally, the conductivity of the flame retardant conductive primer layer is 0.01% to 100%; and / or the roughness of the flame retardant conductive primer layer is 0.8 to 5 μm.

[0016] The invention also discloses a lithium ion battery, comprising the positive electrode sheet.

[0017] The present invention also discloses a method for preparing a positive electrode sheet, which is used for preparing the positive electrode sheet or the lithium ion battery, and comprises the following steps:

[0018] preparing a flame retardant conductive primer slurry;

[0019] Applying the flame retardant conductive primer slurry on the current collector and drying it to form a flame retardant conductive primer;

[0020] preparing a positive electrode active material layer slurry;

[0021] The positive electrode active material layer slurry is coated on the flame retardant conductive primer layer and dried to form a positive electrode active material layer to obtain a positive electrode sheet.

[0022] Compared with the prior art, the positive electrode sheet provided by the embodiment of the present invention has the beneficial effect that: the flame retardant of the present application is preferably aluminum hydroxide. The surface of aluminum hydroxide has corresponding gaps, which can not only improve the safety performance of the positive electrode sheet of the battery cell, but also maintain the good cycle performance of the positive electrode sheet. Aluminum hydroxide satisfies the following relationship: 10≤ρ×r / A≤10000. In ρ×r / A, if ρ×r / A is greater than 10000, the value of ρ×r / A is too large, indicating that the resistivity of aluminum hydroxide is too large and the specific surface area is too small for the present application, which will lead to poor cycle; and the small specific surface area will also lead to insufficient bonding points and poor safety performance of the battery cell; if ρ×r / A is less than 10, the value of ρ×r / A is too small, which means that the resistivity of aluminum hydroxide is too small and the specific surface area is too large, which will make the electrolyte absorption high and the cycle performance better, but the resistance is also small and the safety performance is not improved. Therefore, the flame retardant of the present application is preferably aluminum hydroxide that satisfies 10≤ρ×r / A≤10000, which can ensure both good cycle performance and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments, in which:

[0024] Figure 1 Schematic diagram of a positive electrode sheet according to an embodiment of the present invention.

[0025] The reference numerals in the figures are:

[0026] 1. Current collector; 2. Flame retardant conductive primer layer; 3. Positive electrode active material layer. DETAILED DESCRIPTION

[0027] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. Now, in conjunction with the accompanying drawings, a preferred embodiment of the present invention is described in detail.

[0028] The embodiment of the present invention provides a positive electrode sheet, such as Figure 1 As shown, the positive electrode sheet includes a current collector 1, a flame retardant conductive primer layer 2 and a positive electrode active material layer 3; the flame retardant conductive primer layer 2 is arranged on the surface of the current collector 1, and the positive electrode active material layer 3 is arranged on the flame retardant conductive primer layer 2; the flame retardant conductive primer layer 2 includes a flame retardant and a conductive agent.

[0029] In the positive electrode sheet of the present invention, a flame retardant conductive primer layer 2 is arranged on the current collector 1, and the positive electrode active material layer 3 of the positive electrode sheet is arranged on the flame retardant conductive primer layer 2, and the flame retardant conductive primer layer 2 includes a flame retardant and a conductive agent. In this way, in the face of abuse tests such as lithium ion battery puncture or actual abuse situations, the flame retardant can effectively play its role and maintain the thermal stability of the lithium ion battery, thereby reducing safety accidents. At the same time, in addition to the flame retardant, the flame retardant conductive primer layer 2 is also matched with a conductive agent to improve the safety performance of the battery cell. While improving the safety performance, the conductivity of the positive electrode sheet is not weakened, thereby not deteriorating the relevant electrical properties of the lithium ion battery, and there is no need to use a special thickened diaphragm, thereby reducing costs.

[0030] Furthermore, the flame retardant of the present application is preferably aluminum hydroxide. The surface of aluminum hydroxide has corresponding gaps, which can not only improve the safety performance of the positive electrode sheet of the battery cell, but also maintain the good cycle performance of the positive electrode sheet. Among them, aluminum hydroxide satisfies the following relationship:

[0031] 10≤ρ×r / A≤10000

[0032] Wherein, ρ is the resistivity of aluminum hydroxide, in Ω·m; r is the particle size of aluminum hydroxide, in nm; A is the specific surface area of ​​aluminum hydroxide, in m 2 / g.

[0033] In ρ×r / A, if ρ×r / A is greater than 10000, the value of ρ×r / A is too large, indicating that the resistivity of aluminum hydroxide is too large and the specific surface area is too small for the present application, which will lead to poor cycle performance; and the small specific surface area will also lead to insufficient bonding points and poor safety performance of the battery core; if ρ×r / A is less than 10, the value of ρ×r / A is too small, which means that the resistivity of aluminum hydroxide is too small and the specific surface area is too large, which will make the electrolyte absorption high and the cycle performance better, but the resistance is also small and the safety performance has no improvement effect. Therefore, the flame retardant of the present application is preferably aluminum hydroxide that satisfies 10≤ρ×r / A≤10000, which can ensure both good cycle performance and safety performance.

[0034] Specifically, the particle size of aluminum hydroxide is 1nm to 9um, and the specific surface area is 1 to 5m 2 / g, and the resistivity is 108~1012Ω·m. For example, the particle size of aluminum hydroxide can be 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50um, and the specific surface area can be 0.9m 2 / g, 1m 2 / g, 1.5m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, 5m 2 / g, 5.5m 2 / g, 6m 2 / g, the resistivity can be 108Ω·m, 200Ω·m, 300Ω·m, 400Ω·m, 500Ω·m, 600Ω·m, 700Ω·m, 800Ω·m, 900Ω·m, 1000Ω·m, 1012Ω·m. The conductivity of the flame retardant conductive primer layer is 0.01% to 100%, for example, it can be 0.01%, 0.5%, 1%, 5%, 10%, 15%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%. The roughness of the flame retardant conductive primer layer is 0.8 to 5μm, for example, it can be 0.8μm, 1μm, 2μm, 3μm, 4μm, 5μm.

[0035] Specifically, the flame retardant conductive primer layer 2 is coated on both sides of the current collector 1 , and the positive electrode active material layer 3 is coated on the flame retardant conductive primer layer 2 on both sides of the current collector 1 .

[0036] Aluminum hydroxide has an endothermic effect. It can absorb a large amount of heat during the combustion process, and release water vapor, reduce the combustion temperature, slow down the spread of flames, and play a flame retardant role. Secondly, aluminum hydroxide can decompose and release water vapor at high temperatures, forming a protective layer covering the surface of the positive electrode sheet, isolating oxygen, preventing the spread of fire, and improving flame retardant properties. In addition, aluminum hydroxide has a filling effect, which can increase the hardness and strength of the flame retardant conductive primer 2 and the positive electrode sheet, and improve the mechanical properties of the flame retardant conductive primer 2 and the positive electrode sheet. At the same time, as an inorganic material, aluminum hydroxide is environmentally friendly, does not contain organic matter, does not produce toxic gases, and meets environmental protection requirements. In addition, aluminum hydroxide has good chemical stability and thermal stability, can maintain the structural integrity of the positive electrode sheet under high temperature conditions, and extend the service life of the positive electrode sheet.

[0037] The conductive agent is one or more of conductive carbon black, graphene, carbon nanotubes, carbon nanorods, graphite, etc. Conductive carbon black, graphene, carbon nanotubes, and graphite have excellent conductive properties, which are helpful to optimize the structure of the flame retardant conductive primer layer 2, can effectively improve the conductivity of the flame retardant conductive primer layer 2, improve the electron transmission efficiency of the positive electrode sheet, and reduce the resistance.

[0038] By mass percentage, the proportion of flame retardant in the flame retardant conductive primer 2 is 10% to 90%. A high content of flame retardant can effectively improve the ability to prevent the coating from burning, thereby improving the safety of lithium-ion batteries when facing high temperatures or external fire sources. Increasing the content of flame retardant can reduce the burning rate of the flame retardant conductive primer 2, delay the time for the spread of flames, and improve the safety of lithium-ion batteries. An appropriate amount of flame retardant content can maintain the conductive properties of the flame retardant conductive primer while improving safety, avoiding negative effects on the overall performance of lithium-ion batteries. Specifically, the proportion of flame retardant in the flame retardant conductive primer 2 can be any of 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, and 90%.

[0039] In terms of mass percentage, the conductive agent accounts for 5% to 35% in the flame retardant conductive primer layer 2. An appropriate amount of conductive agent can effectively improve the conductive properties of the flame retardant conductive primer layer, while ensuring the flame retardant properties of the flame retardant conductive primer layer 2. Specifically, the conductive agent accounts for any of 5%, 10%, 15%, 20%, 25%, 30%, and 35% in the flame retardant conductive primer layer 2.

[0040] Furthermore, the flame retardant conductive primer layer 2 further includes a binder, and the binder is one or more of polyvinylidene fluoride (PVDF), polyimide (PI), polyamide (PA), polyacrylonitrile (PAN), polyacrylamide (PAM), etc. The amount of the binder in the flame retardant conductive primer layer 2 added to the flame retardant conductive primer layer 2 is the remainder after adding the flame retardant and the conductive agent.

[0041] The thickness of the flame retardant conductive primer layer 2 is 1 um to 10 um, and specifically can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm.

[0042] Further, the positive electrode active material layer 3 includes lithium cobalt oxide, conductive carbon black and polyvinylidene fluoride.

[0043] The invention also discloses a lithium ion battery, comprising the positive electrode sheet.

[0044] The present invention also discloses a method for preparing a positive electrode sheet, which is used for preparing the positive electrode sheet or the lithium ion battery, and comprises the following steps:

[0045] preparing a flame retardant conductive primer slurry;

[0046] Applying the flame retardant conductive primer slurry on the current collector and drying it to form a flame retardant conductive primer;

[0047] preparing a positive electrode active material layer slurry;

[0048] The positive electrode active material layer slurry is coated on the flame retardant conductive primer layer and dried to form a positive electrode active material layer to obtain a positive electrode sheet.

[0049] The technical solution of the present invention is further illustrated by specific embodiments below.

[0050] Comparative Example 1

[0051] According to the addition amount of each component in Table 1 below, lithium cobalt oxide, conductive carbon black, and binder PVDF were added into NMP and stirred to prepare a positive electrode active material layer slurry with a solid content of 30%.

[0052] The positive electrode active material layer slurry is coated on an aluminum foil with a thickness of 13 μm and dried to form a positive electrode sheet;

[0053] Adding graphite, CMC and SBR in a mass ratio of 98:1:1 to deionized water and stirring to prepare a negative electrode active material layer slurry with a solid content of 30%;

[0054] The negative electrode active material layer slurry is coated on a copper foil with a thickness of 6 μm and dried to form a negative electrode sheet;

[0055] The positive electrode sheet, the separator, the negative electrode sheet and the electrolyte are assembled to obtain a lithium-ion battery.

[0056] Comparative Example 2

[0057] According to the addition amount of each component in Table 1 below, the components of the flame retardant conductive primer were mixed and stirred for 15 minutes, NMP was added to adjust the solid content to 30%, and secondary dispersion was performed for 60 minutes to obtain a flame retardant conductive primer slurry.

[0058] The flame retardant conductive primer slurry is applied on an aluminum foil with a thickness of 13 μm and dried to obtain a flame retardant conductive primer.

[0059] According to the addition amount of each component in Table 1 below, lithium cobalt oxide, conductive carbon black, and binder PVDF were added into NMP and stirred to prepare a positive electrode active material layer slurry with a solid content of 30%.

[0060] The positive electrode active material layer slurry is coated on the flame retardant conductive primer layer and dried to form a positive electrode sheet;

[0061] Adding graphite, CMC and SBR in a mass ratio of 98:1:1 to deionized water and stirring to prepare a negative electrode active material layer slurry with a solid content of 30%;

[0062] The negative electrode active material layer slurry is coated on a copper foil with a thickness of 6 μm and dried to form a negative electrode sheet;

[0063] The positive electrode sheet, the separator, the negative electrode sheet and the electrolyte are assembled to obtain a lithium-ion battery.

[0064] Comparative Examples 3-4

[0065] The addition amounts of each component of the positive electrode sheet of Comparative Example 3-4 are as shown in Table 1. Except for the different addition amounts of each component in Table 1, the remaining preparation steps and component amounts are the same as those of Comparative Example 2, which will not be repeated here.

[0066] Example 1

[0067] According to the addition amount of each component in Table 1 below, the components of the flame retardant conductive primer were mixed and stirred for 15 minutes, NMP was added to adjust the solid content to 30%, and secondary dispersion was performed for 60 minutes to obtain a flame retardant conductive primer slurry.

[0068] The flame retardant conductive primer slurry is applied on an aluminum foil with a thickness of 13 μm and dried to obtain a flame retardant conductive primer.

[0069] According to the addition amount of each component in Table 1 below, lithium cobalt oxide, conductive carbon black, and binder PVDF were added into NMP and stirred to prepare a positive electrode active material layer slurry with a solid content of 30%.

[0070] The positive electrode active material layer slurry is coated on the flame retardant conductive primer layer and dried to form a positive electrode sheet;

[0071] Adding graphite, CMC and SBR in a mass ratio of 98:1:1 to deionized water and stirring to prepare a negative electrode active material layer slurry with a solid content of 30%;

[0072] The negative electrode active material layer slurry is coated on a copper foil with a thickness of 6 μm and dried to form a negative electrode sheet;

[0073] The positive electrode sheet, the separator, the negative electrode sheet and the electrolyte are assembled to obtain a lithium-ion battery.

[0074] Example 2

[0075] The addition amounts of each component of the positive electrode sheet of Example 2 are as shown in Table 1. Except for the different addition amounts of each component in Table 1, the remaining preparation steps and component amounts are the same as those of Example 1 and will not be repeated here.

[0076] The lithium ion batteries prepared in Comparative Examples 1-4 and Examples 1-2 were subjected to cycle tests and needle penetration tests. The methods are as follows. The test results are shown in Table 1.

[0077] Cycle test: Place the lithium-ion battery in a 25°C environment for 8 hours, then perform a 1C charge / 1.5C discharge cycle with a voltage of 3.0-4.2 V. When the capacity retention rate reaches 80% SOC, the cycle ends and the number of cycles is recorded.

[0078] Needle puncture test: Fully charge the lithium-ion battery, and use a high-temperature resistant steel needle with a diameter of 5mm to penetrate the lithium-ion battery at a speed of 25mm / s from the direction perpendicular to the lithium-ion battery plate. The penetration position should be close to the geometric center of the punctured surface. The steel needle stays in the lithium-ion battery and is observed for 1 hour. During this period, the lithium-ion battery is considered qualified if it does not catch fire or explode. 30 lithium-ion batteries are tested for each comparative example and embodiment, and the needle puncture pass rate is calculated.

[0079] Table 1

[0080]

[0081] It can be seen from the data in Table 1 above that the cycle life of comparative examples 1-4 is between 380 and 600 weeks, while the cycle life of embodiments 1-2 is 600 weeks, wherein the needle puncture pass rate of aluminum hydroxide in embodiment 1 is 45%, which is better than 43% of the silicon compound in embodiment 2.

[0082] The needle puncture test results show that the needle puncture pass rate of Example 1 is higher than that of Comparative Examples 1-4. This indicates that after adding aluminum hydroxide as a flame retardant, the safety of the lithium-ion battery is improved, especially in Example 1, which can ensure that the cycle life is not deteriorated or better than that of Comparative Examples 1-4, the needle puncture pass rate reaches 45%, which is better than 43% of the silicon compound in Example 2, and is far better than Comparative Examples 1-4. The safety of the lithium-ion battery is significantly improved without deteriorating the cycle electrical performance of the lithium-ion battery.

[0083] The present application further illustrates the technical solution in which the flame retardant is aluminum hydroxide through specific examples 13-22.

[0084] Example 3-12

[0085] The addition amounts of each component and each parameter of the flame-retardant conductive primer layer of Example 3-12 are shown in Table 2. The remaining preparation steps and component amounts are the same as those of Example 1 and will not be repeated here.

[0086] Table 2

[0087]

[0088]

[0089] As shown in the comparison between the embodiment of Table 2 and the comparative examples 1-4 in Table 1, after adding aluminum hydroxide, the conductivity of the electrode piece decreases, and the conductivity deteriorates during the abuse test, so the safety test performance is improved. At the same time, aluminum hydroxide has no lithium ion deintercalation function, while lithium iron phosphate has the charging and discharging function. When lithium iron phosphate primer is used, the flame retardant conductive primer and the active layer of the electrode piece are both charging and discharging, and the consistency of the upper and lower layers of the electrode piece deteriorates, so the cycle and other electrical properties deteriorate. At the same time, the addition of aluminum hydroxide leads to an increase in the roughness of the flame retardant conductive primer layer, tighter bonding, and a corresponding positive effect on the cycle. Specifically, the cycle life of Examples 3-12 is better than or maintains a comparable level, and the needle puncture pass rate can be stabilized in the range of 45%-51%, which is much better than the needle puncture pass rate of Comparative Examples 1-4.

[0090] It should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. For those skilled in the art, the technical solutions described in the above embodiments can be modified, or some of the technical features therein can be replaced by equivalents; and all these modifications and replacements should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A positive electrode sheet, characterized in that: It comprises a current collector, a flame retardant conductive primer layer and a positive electrode active material layer; the flame retardant conductive primer layer is arranged on the surface of the current collector, and the positive electrode active material layer is arranged on the flame retardant conductive primer layer; the flame retardant conductive primer layer comprises a flame retardant and a conductive agent; The flame retardant is aluminum hydroxide, and the aluminum hydroxide satisfies the following relationship: 10≤ρ×r / A≤10000 Wherein, ρ is the resistivity of aluminum hydroxide, in Ω·m; r is the particle size of aluminum hydroxide, in nm; A is the specific surface area of ​​aluminum hydroxide, in m 2 / g.

2. The positive electrode sheet according to claim 1, characterized in that: The particle size of the aluminum hydroxide is 1nm to 9um, and the specific surface area is 1 to 5m 2 / g, resistivity is 10 8 ~10 12 Ω·m.

3. The positive electrode sheet according to claim 2, characterized in that: The conductive agent is one or more of conductive carbon black, graphene, carbon nanotubes, carbon nanorods, and graphite.

4. The positive electrode sheet according to claim 1, characterized in that: Calculated by mass percentage, the flame retardant accounts for 10% to 90% of the flame retardant conductive primer layer.

5. The positive electrode sheet according to claim 4, characterized in that: Calculated by mass percentage, the conductive agent accounts for 5% to 35% of the flame retardant conductive primer layer.

6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The thickness of the flame retardant conductive primer layer is 1um to 10um.

7. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The flame retardant conductive primer layer also includes a binder, which is one or more of polyvinylidene fluoride, polyimide, polyacetamide, polyacrylonitrile and polyacrylamide.

8. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The conductivity of the flame retardant conductive primer layer is 0.01% to 100%; and / or The roughness of the flame retardant conductive primer layer is 0.8-5 μm.

9. A lithium ion battery, characterized in that: A positive electrode sheet comprising any one of claims 1 to 8.

10. A method for preparing a positive electrode sheet, used for preparing the positive electrode sheet according to any one of claims 1 to 8, or for preparing the lithium ion battery according to claim 9, characterized in that: Includes steps: preparing a flame retardant conductive primer slurry; Applying the flame retardant conductive primer slurry on the current collector and drying it to form a flame retardant conductive primer; preparing a positive electrode active material layer slurry; The positive electrode active material layer slurry is coated on the flame retardant conductive primer layer and dried to form a positive electrode active material layer to obtain a positive electrode sheet.